Rotary Jet-Spun Polycaprolactone/Hydroxyapatite and Carbon Nanotube Scaffolds Seeded with Bone Marrow Mesenchymal Stem Cells Increase Bone Neoformation - Machado-Paula, Mirian M.; Corat, Marcus A. F.; De Vasconcellos, Luana M. R. [UNESP]; Araújo, Juliani C. R. [UNESP]; Mi, Gujie; Ghannadian, Paria; Toniato, Tatiane V.; Marciano, Fernanda R.; Webster, Thomas J.; Lobo, Anderson O. (American Chemical Society (ACS), 2022)
Clinically, bone tissue replacements and/or bone repair are challenging. Strategies based on well-defined combinations of osteoconductive materials and osteogenic cells are promising to improve bone regeneration but still require improvement. Herein, we combined polycaprolactone (PCL) fibers, carbon nanotubes (CNT), and hydroxyapatite (nHap) nanoparticles to develop the next generation of bone regeneration material. Fibers formed by rotary jet spinning (RJS) instead of traditional electrospinning (ES) with embedded bone marrow mesenchymal stem cells (BMMSCs) showed the best outcomes to repair rat calvarial defects after 6 weeks. To understand this, it was observed that different morphologies were formed depending on the manufacturing method used. RJS fibers presented a particular topography with rough fibers, which allowed for better cellular growth and cell spreading in vitro around and into a three-dimensional (3D) mesh, while fibers made by ES were more smooth and cellular growth was only measured on the 3D mesh surface. The fibers with incorporated nHap/CNT nanoparticles enhanced in vitro cell performance as indicated by more cellular proliferation, alkaline phosphatase activity, proliferation, and deposition of calcium. Greater bone neoformation occurred by combining three characteristics: the presence of nHap and CNT nanoparticles, the topography of the RJS fibers, and the addition of BMMSCs. RJS fibers with nanoparticles and seeded with BMMSCs showed 10136 mm3of bone neoformation, meaning a 10-fold increase compared to using RJS only and BMMSCs (0.853 mm3) and a 5-fold increase from using ES only (2054 mm3) after 6 weeks of implantation. Conversely, none of these approaches used individually showed any significant difference for in vivo bone neoformation, suggesting that their combination is essential for optimizing bone formation. In summary, our work generated a potential material composed of well-defined combinations of suitable scaffolds seeded with BMMSCs for enhancing numerous orthopedic tissue engineering applications.
Keywords: bone marrow mesenchymal stem cells; carbon nanotubes; electrospinning; nanohydroxyapatite; osteoblast differentiation; polycaprolactone; rotary jet spinning